1991
DOI: 10.1093/ajcn/53.4.1031s
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional evaluation of crude palm oil in rats

Abstract: Edible-grade crude palm oil (CPO: from Elaeis guineensis) is one of the richest natural sources of beta-carotene (7500 mumol/L) and is cheaper than other edible oils, making it a promising source of vitamin A in a deficient population. Nutritional studies were conducted on weanling albino rats of the Wistar/NIN strain for 28 and 90 d. Diets contained 10% of either CPO, groundnut oil (GNO), or refined palm-olein oil (RPO) and adequate amounts of all other nutrients. No adverse effects were observed as judged by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 6 publications
4
27
1
Order By: Relevance
“…Triglycerides were augmented in the animals fed with the tested oils. A similar result was found by Manorama and Rukmini (1991) when testing the crude and refined palm oils against the groundnut oil in the rats during 28 days. Nevertheless, when the animals were examined after 90 days of experiment, the TG values were statistically equal amongst all the groups.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Triglycerides were augmented in the animals fed with the tested oils. A similar result was found by Manorama and Rukmini (1991) when testing the crude and refined palm oils against the groundnut oil in the rats during 28 days. Nevertheless, when the animals were examined after 90 days of experiment, the TG values were statistically equal amongst all the groups.…”
Section: Resultssupporting
confidence: 83%
“…The moringa oil contains a diversity of fatty acids that enables it to fulfill the needs of the animals in the 28-day assay (Banerji et al, 2009;Elkhalifa et al, 2007). A similar pattern was observed by Manorama and Rukmini (1991), when studying the performance of crude palm oil in the rats in equivalent conditions. Other unusual oils, such as coriander (Mironova et al, 1991) and grape seed (Mironova et al, 1990) were studied using the rats and both were shown to be equivalent to sunflower oil as far as biological properties were concerned.…”
Section: Resultssupporting
confidence: 83%
“…The fruit also contains components such as carotenoids (alpha, beta, and gamma carotenes), vitamin E (tocophoreols and tocotrienols), sterols (sitosterol, stigmasterol and campesterol), phospholipids, glycolipids and squalene, which are of known nutritional and health benefits (Wattanapenpaiboon and Wahlqvist, 2003;Manorama and Rukmini (1991). In addition, it has been reported that certain powerful water-soluble antioxidants, phenolic acids and flavonoids can be recovered from the palm oil mill effluents (Abeywardena et al, 2002;Balasundram et al, 2003;Yun et al, 2008).…”
mentioning
confidence: 99%
“…These phytonutrients (i.e. tocotrienols and carotenes) are also powerful anti-oxidants that help maintain the stability of the oil during cooking process and may extend the shelf life of food prepared with red palm oil Research has shown that consumption of red palm oil significantly enhanced vitamin A levels in humans, and it is beneficial in preventing vitamin A deficiency (Manorama and Rukmini, 1991;Roo, 2000;Solomons, 1998) and it is used for combating vitamin A deficiency in developing countries (Rukmini, 1994). Additionally, some workers have advised that nursing mothers should take red palm oil as supplement with their food in order to prevent vitamin A deficiency (Lietz et al, 2000).…”
Section: Anti-oxidant Activitymentioning
confidence: 99%